Reduction in Brain Parenchymal Volume Correlates with Depression and Cognitive Decline in HIV-Positive Males - Radmila Perić; Duško Kozić; Snežana Brkić; Dajana Lendak; Jelena Ostojić; Vojislava Bugarski Ignjatović; Jasmina Boban (Medicina)
Background and Objectives: Human immunodeficiency virus (HIV) has a profound impact on the central nervous system (CNS), contributing to cognitive impairment and depressive symptoms even in individuals receiving combination antiretroviral therapy (cART). This study aimed to investigate the associations between brain parenchymal volumes and neuropsychological outcomes, specifically focusing on cognitive function and depressive symptoms in HIV-positive males. Materials and Methods: A total of 48 male participants underwent cognitive assessment using the Mini-Mental State Examination (MMSE), while depressive symptoms were evaluated in 35 participants using the Beck Depression Inventory (BDI). Volumetric brain analysis was conducted through automated imaging software, volBrain (Version 1.0, published on 23 November 2021), ensuring high consistency and accuracy. Statistical analyses included Pearson correlation to identify relationships between brain volumes and neuropsychological outcomes, emphasizing key regions like the basal forebrain and cingulate gyrus. Results: Significant trends were observed between basal forebrain volume and MMSE scores, emphasizing the role of this region in cognitive regulation. Additional correlations were found with the anterior and middle cingulate gyri, which are crucial for executive functioning and attentional control. Notably, smaller right basal forebrain volumes were associated with greater depressive symptom severity, suggesting the region’s specific involvement in mood regulation. These findings highlight the dual impact of HIV on cognitive and emotional health, with structural vulnerabilities in key brain regions playing a central role. Conclusions: This study underscores the selective vulnerability of certain brain regions, such as the basal forebrain and cingulate gyrus, to HIV-associated neurodegeneration. The results highlight the importance of integrating neuroimaging and neuropsychological assessments in routine clinical care for HIV-positive individuals. The study emphasizes the importance of early detection and targeted interventions to address neuropsychological challenges in this population, with a call for further research in larger and more diverse cohorts.